Properties of as-prepared and freeze-dried hydrogels made from poly(vinyl alcohol) and cellulose nanocrystals using freeze-thaw technique. (August 2016) - Butylina, Svetlana; Geng, Shiyu; Oksman, Kristiina
Graphical abstract: Highlights: PVA hydrogels reinforced with CNC were produced by using freeze-thaw procedure. Synergetic effect on E50% and σ50% was found between addition of CNC and increase in PVA concentration. An addition of CNC increased degree of swelling of rehydrated hydrogels. Rehydrated hydrogels showed better compressive properties than as-prepared hydrogels. Abstract: Poly(vinyl alcohol), PVA hydrogels are potential materials for biomedical and biotechnogical applications. However, their low mechanical properties restrict their use. In this study, the effect of PVA concentration, addition of nanocrystalline cellulose, CNC, number of freeze-thaw cycles and freeze-drying stage on properties of resulting hydrogels were investigated. The results showed that increase in PVA concentration and the addition of CNC improved the compressive properties of the hydrogels. Overall, increase in number of freeze-thaw cycles from 3 to 5 did not show any improvements in properties of hydrogels. Concentration of PVA had great effect on morphology of freeze-dried hydrogels. The CNC reduced crystallinity of PVA/CNC hydrogels as compared to PVA hydrogels. Rehydrated PVA and PVA/CNC hydrogels had higher compressive characteristics than their as-prepared analogues. In general, an improvement of compressive properties of hydrogels was achieved via reduction of their water content. In case of 5% PVA hydrogel, an addition of CNC was found to be beneficial because it increased degree of swelling and water content on rehydration.